Network-based information systems : first international conference, NBiS 2007, Regensburg, Germany, September 3-7, 2007 : proceedings - NBiS 2007 (2007 : Regensburg, Germany); Enokido, Tomoya; Barolli, Leonard; Takizawa, Makoto (Berlin : Springer-Verlag, 2007)
13